2007
DOI: 10.1007/s10856-007-3293-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thin carbonate-containing apatite (CA) coating of titanium fiber mesh on trabecular bone response

Abstract: The influence of thin carbonate-containing apatite (CA) coating on trabecular bone response to cylindrical titanium fiber mesh (porosity of 85%, pore size of 200-300 microm, 2.8 mm diameter x 6 mm length) implants was investigated. Thin CA coatings were deposited by the so-called molecular precursor method. Molecular precursor solution was obtained by adding dibutylammonium diphosphate salt to Ca-EDTA/amine ethanol solution by adjusting Ca/P = 1.67. Sintered cylindrical titanium fiber mesh was immersed into mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 27 publications
2
31
0
Order By: Relevance
“…Adherent HA coating of several micrometers could be easily deposited on titanium. It is possible to deposit uniform apatite coating onto three-dimensional complexly shaped materials, such as porous materials 23) . In the present study, uniform apatite coating could be deposited not only on the root surface but also on the root furcation of tooth-shaped titanium implants by an immersion and heating process.…”
Section: Miller's Classificationmentioning
confidence: 99%
“…Adherent HA coating of several micrometers could be easily deposited on titanium. It is possible to deposit uniform apatite coating onto three-dimensional complexly shaped materials, such as porous materials 23) . In the present study, uniform apatite coating could be deposited not only on the root surface but also on the root furcation of tooth-shaped titanium implants by an immersion and heating process.…”
Section: Miller's Classificationmentioning
confidence: 99%
“…Hanawa et al 15,16) also found that apatite formed on a titanium surface after immersion in Hank's balanced salt solution (HBSS) without organic species at pH=7.4 and reported on the efficacy of HBSS as an SBF. Hayakawa et al 17) demonstrated apatite formation on a thin Ca coated titanium fiber mesh surface after immersion in HBSS by a thin Ca coating using the molecular precursor method. Thus, previous results reported by Kitahara et al 8) suggested that hydrolyzed PLA will be effective for bone formation because of the progression of apatite precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the dissolution of Ca 2+ from the coating forms a supersaturated interface condition, followed by the deposition a mineral layer. The molecular precursor method is a simple technique in which a uniform coating of thin HA on the TW is easily achieved 13,21) . Previously, a biomimetic process using simulated body fluid was reported 22,23) .…”
Section: Discussionmentioning
confidence: 99%